الجانب العرفاني في مفهوم الاستعارة عند الجاحظ. - كريوش, ابراهيم (University of Eloued جامعة الوادي, 2021)
يسعى هذه الجهد إلى الوقوف على مفهوم الاستعارة عند الجاحظ، بما أنه هو أول من وضع تعريفا لها في البلاغة العربية، وبغض النظر عن قيمة هذا التعريف، يكفي أنه كان واعيا تمام الوعي بهذا النوع من الصور، وقد عالجه وفق رؤية موسعة وشاملة(المجاز)، تتفق مع مذهبه وتصوره للبيان العربي. وقد كان واعيا كذلك بالمراحل الذهنية والعقلية التي تتشكل من خلالها هذه الصورة، والاعتبارات والعوامل التي تتدخل في تكوينها، والغايات التي تسعى إلى تحقيقها، بعد أن تخرج في صورتها النهائية. وقد حاولنا من خلال عملنا هذا أن نبحث عن نقاط تقارب أو تماس بين آراء الجاحظ، وآراء المعاصرين الذين عالجوا الاستعارة وفق تصور عرفاني واسع الأفق، مستفيدين من نتائج علوم مختلفة تدعى بالعلوم العرفانية (علم الأعصاب، علم النفس، الذكاء الاصطناعي، فلسفة الذهن، علوم الحاسوب، الأنسنة الإدراكية، واللسانيات العرفانية). This effort seeks to identify the concept of metaphor for al-Jahiz, since he was the first to define it in Arabic rhetoric, and regardless of the value of this definition, it is sufficient that he was fully aware of this type of image, and he treated it according to an expanded and comprehensive vision (al-Majaz), Consistent with his doctrine and his conception of the Arab statement. He was also aware of the mental and mental stages through which this image is formed, the considerations and factors that interfere in its formation, and the goals that it seeks to achieve, after it emerges in its final form/ Through our work, we have tried to search for points of convergence or contact between the views of Al-Jahiz and the opinions of contemporaries who have treated the metaphor according to a broad-minded customary conception, making use of the results of different sciences called secular sciences (neuroscience, psychology, artificial intelligence, philosophy of mind, Computer science, Perceptual Humanism, and Cognitive Linguistics).
Keywords: العرفانية، التداولية، الاستعارة، التشبيه، الجاحظ. ; Citizenship; deliberative; Metaphor; Simile; al-Jahiz.